Price quotation system (PQS) - Adyosmera, Lidin; Azahari, Mohd Zaman; Azlan, Mortadza; Dayang Asma, Abang Mohammad; Fizalyhan, Sadie (Faculty of Computer Science and Information Technology, 2003)
Today's business arena has foreseen many increasing usage on new technology, such as sophisticated business software and high-tech gadgets. By making fall use of the opportunity offered by this type of information technology, a company or a corporate sector can better enhance their services that can be an addition to their advantages.